2001
DOI: 10.1074/jbc.m106123200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Multiple Protein Domains and Residues for GatingKATP Channels by Intracellular pH

Abstract: ATP-sensitive K؉ channels (K ATP ) are regulated by pH in addition to ATP, ADP, and phospholipids. In the study we found evidence for the molecular basis of gating the cloned K ATP by intracellular protons. Systematic constructions of chimerical Kir6.2-Kir1.1 channels indicated that full pH sensitivity required the N terminus, C terminus, and M2 region. Three amino acid residues were identified in these protein domains, which are Thr-71 in the N terminus, Cys-166 in the M2 region, and His-175 in the C terminus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…The Kir6.2 channels are also activated by intracellular H ϩ (30). The pH-dependent channel gating requires both N and C termini, although there is only one protonation site (His-175) located in the C terminus (21,31). The importance of the proximal N terminus in channel gating has been studied with different ligands, indicating that this region is indeed involved in Kir6.2 channel gating rather than ligand binding (32,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Kir6.2 channels are also activated by intracellular H ϩ (30). The pH-dependent channel gating requires both N and C termini, although there is only one protonation site (His-175) located in the C terminus (21,31). The importance of the proximal N terminus in channel gating has been studied with different ligands, indicating that this region is indeed involved in Kir6.2 channel gating rather than ligand binding (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…The cDNAs were cloned in the eukaryotic expression vector pcDNA3.1 and used for mammalian cell expression (5, 6). Kir6.1-Kir6.2 chimeras were produced by overlap extension using PCR (Pfu DNA polymerase; Stratagene, La Jolla, CA) (21). Site-specific mutations were made using a site-directed mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…Functional studies have demonstrated that the mutations identified in patients with syndromic PNDM (V59G, G52R, I296L) result in a larger K ATP current and greater change in ATP sensitivity than those which cause PNDM alone (R201C), suggesting that larger K ATP currents are required to influence extrapancreatic cell function. 9,15 Residue C166 has been extensively mutated 16,17 and functional studies have shown that the C166F mutation results in a channel with a marked increase in open probability (0.77 vs 0.11) and a reduced ATP sensitivity (Ki ATP , 5.3 mM vs wild type 175 mM) where Ki ATP is the ATP concentration at which inhibition is half-maximal. 17 The fact that the channel open probability is increased implies a role for this residue in channel gating.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Cys166 located in the transmembrane 2 region (Supplemental Fig. S1) is known to participate in the channel gating or the final stage of signal transduction, because the C166S mutation disrupts K ATP channel gating by ATP, proton, and sulfonylurea Piao et al, 2001;Wu et al, 2004). Likewise, the Thr71 at the intracellular end of the transmembrane 1 region is likely to act in channel gating by ATP and protons as well (Cui et al, 2003;Wang et al, 2005b).…”
Section: Atp-sensitive Kmentioning
confidence: 99%